Tirotropina and its correlation with cholesterol and triglycerids in healthy patients and with subclinical thyroid dysfunction - León, Enrique (2020)
Objective: To correlate the levels of thyrotropin with the levels of cholesterol and serum triglycerides in 250 healthy subjects and patients with subclinical thyroid dysfunction with a minimum fasting of 8 hours. Methodology: Analytical methods: total cholesterol, triglycerides: Enzyme-colorimetric and Thyrotropin: ELISA immunoenzymatic. Results: Thyrotropin was found in healthy subjects 88,68% in men and 89,34% in women, in patients with hyper thyroid dysfunction 1,89% for men and 1,52% for women, as well as hypo 9,43% for men and 9,14% for women. Cholesterol in healthy subjects for men is 49,06% and in women 67,01%; in patients with hyper thyroid dysfunction 50,94% for men and 32,99% for women. Triglycerides in healthy subjects 69,81% in men and 62,44% in women, in patients with hyper thyroid dysfunction 30,19% for men and 37,56% in women. Conclusions: A correlation was found between thyrotropin and cholesterol (p <0,05), this is due to an increase in the number of low-density lipoprotein liver receptors (LDL-col), which accelerates its clearance, was not found correlation between thyrotropin and triglycerides (p> 0,05), cholesterol concentrations are high in subjects with hypothyroidism.